Conceptualization of Holistic Learning in Islamic Basic Education to Improve Cognitive and Spiritual Balance - Mikhael Klemens Kedang (Journal of Islamic Elementary Education, 2026)
This study aims to examine and formulate the conceptualization of holistic learning in Islamic basic education as an effort to enhance the balance between cognitive and spiritual aspects of students. The study employs a qualitative approach with a conceptual research design (library research), utilizing various sources such as academic books, national and international journal articles, and educational policy documents. Data were collected through documentation techniques and analyzed using content analysis, including data reduction, categorization, synthesis, and conclusion drawing. The findings reveal that holistic learning in Islamic basic education emphasizes the integration of cognitive, affective, and spiritual dimensions within the learning process. Learning models such as Problem Based Learning, Project Based Learning, and contextual learning are considered relevant in supporting this approach. Furthermore, holistic learning has a positive impact on improving critical thinking skills, character building, and strengthening students’ religious awareness. Therefore, the conceptualization of holistic learning can serve as both a theoretical and practical foundation in developing Islamic basic education that is balanced, integrative, and oriented toward the formation of a complete human being.